Peran Movie Image Terhadap Pemilihan Destinasi - Redly Candra Juntana (Universitas Multimedia Nusantara, 2018)
Abstract-This study aims to test whether the film is pivotal in the development of Empathy, Nostlagia, Perceived Risk, Place Familiarity, Place Image that can shape Attitude Towards and Intention to Visit A ​​place. The study was conducted using Structural Equation Model (SEM) and processed with the help of Statistical Package for Social Sciences (SPSS) version 23 and AMOS 24. 200 respondents were taken from respondents who had watched the Harry Potter movie series more than once, still remember the scenery from Hogwarts school (Alnwick Castle), and known that Alnwick castle is used as a tourist destination. The results show that Empathy, Nostalgia, Place Familiarity, Place Image are factors that significantly positively affect Attitude and Intention on Alnwick castle. Perceived Risk is a factor that has no significant effect on Place Familiarity at Castle Alnwick. The respondents who had watched the Harry Potter movie series had a positive Attitude and had an Intention to visit Alnwick castle. Keywords: Perception, Movies, Destination Image, Risk, Intention, Familiarity.